OTA (Online Travel Agent) Purchase Decision From Risk Perception With E-Trust As An Intervening: Keputusan Pembelian OTA (Online Travel Agent) Dari Persepsi Risiko Dengan E-Trust Sebagai Intervening - Fajar Kamil Pasya; Febriani Nur Islami; Nisa Hanifah; Khairani Zikrinawati; Zulfa Fahmy (Journal of Multidisciplinary Science, 2023)
The increasing number of Online Travel Agent (OTA) services in this digital era was caused by the diverse consumer behavior in choosing their preferred Online Travel Agent (OTA) services. However, in making purchasing decision, customers need to consider all of the risks that exist since there are several transaction risks that are hard to avoid. This study aims to determine the effect of online transaction trust (e-trust) as an intervening variable between perceived risk and purchasing decision, and to determine the effect between risk perception and e-trust on purchasing decision for Online Travel Agent (OTA) customers. This study used a quantitative research design. This research used a questionnaire which was presented in the form of a likert scale. There were 158 respondents as subjects in this study. The sampling method used in this research is purposive sampling. This research used several tests such as validity, reliability, classical assumption, and path analysis. The results showed that e-trust has an effect as an intervening variable between perceived risk and purchasing decisions proven by the amount of 0,409 > 0,340.